Pseudo-Plato. Definitions - Platonas, Pseudo - (Problemos, 2016)
Versta iš: Definitiones [Sp.], in: Platonis opera, ed. J. Burnet, Vol. 5, Oxford: Clarendon Press, 1907. St III. 411a–416a.Iš sen. graikų kalbos vertė filosofinio teksto vertimo seminaro dalyviai:Vytautas Ališauskas, Vilius Bartninkas, Žygintas Beručka, Paulius Garbačiauskas, Vilius Kubekas, Aistė Noreikaitė, Virgilijus Petuška, Gendvilė Svirskaitė, Gintarė Vaičiulytė, Raminta VažgėlaitėParengė Paulius Garbačiauskas